Кремневый инвентарь местонахождения Траповка - Пиструил, И.В. (Материалы по археологии Северного Причерноморья, 2015)
The location of Trapovka was discovered by G.N. Toschev in 1973. The location is situated on the eastern shore of lake (lagoon) Sasyk (Kunduk), 4–6 metres above water boundary, at the southern periphery of Trapovka village. Over 500 flint implements were collected from the area 50 u 50 metres. Preliminary publications of finds were constantly used for illustration of cultural-historic process in North-West Pontic region. General characteristics of flint inventory allowed to attribute it to Kukrek-type sites of Late Mesolithic time. In this paper the analysis of flint inventory of Trapovka location is presented. The conclusion is that the collection has mixed character and consists of finds related to different chronology (from Mesolithic to present time).